The concept of self-defence in Islamic jurisprudence - Owaydhah, Khalid A.; Mohamad Yunus, Mohamad Ismail (University Publications, USA, 2017)
The purpose of this paper to delineate and explore the concept of self-defence in Islamic jurisprudence from various perspectives. That is, self-defence is to be scrutinised as both a general concept of Islamic jurisprudence and a specific idea of various schools of Islamic law, such as Sunni schools of Sahfii, Hanbali, Maliki, and Hanafi. Given this, the current study is purposed to provide comprehensive answers to a series of research questions. Thus, the primary question of research should be formulated as follows: What is the legal basis for self-defence under Islamic jurisprudence? To continue, the secondary question of research should be articulated as follows: What are the principles of self-defence under Islamic jurisprudence? The last but not least, the tertiary question of research should be stated as follows: What are the specificities of the practical application of the principles of self-defence by Islamic jurists, judges, lawyers and other participants of the legal process? After everything has been given due consideration, it is necessary to generalise that self-defence under Islamic jurisprudence has specific legal basis, specific principles, and peculiarities in their practical application of these principle by different schools of Islamic legal thought. It was ascertained that not only self-defence, but also killing in self-defence The first and foremost principle stipulates that killing in self-defence is permissible under Islamic jurisprudence and neither blood money nor retribution is mandatory if an attacker takes action to kill the defender, while the defender is deprived of any opportunity to escape albeit he has taken strenuous efforts to escape and consequently is forced by the circumstances to kill the attacker.